Pengaruh Attitude Subjective Norms, dan Perceived Behavioural Control Terhadap Minat Investor Berinvestasi Cryptocurrency - Muhammad Muhammad; Driana Leniwati; Agung Muhammadiyah Prasetyo N.W; Ahmad Juanda; Endang Dwi Wahyuni; Setu Setyawan (Department of Accounting, Faculty of Economics & Business, 2023)
This research is motivated by the increase in the number of investors from 2019-2021. This increase indicates that the Indonesian people have become increasingly interested to invest in cryptocurrencies while the price of cryptocurrency is very volatile so that it can be formulated in this study what factors cause investors to be interested to invest in cryptocurrencies based on attitude, subjective norms and perceived behavioral control. This study aims to determine the effect of attitude, subjective norms and perceived behavioural control on the intention to invest in cryptocurrency. This study used a quantitative approach with primary data of survey questionnaire to collect from a sample of 81 respondents using non probability with convenience sampling method. The collected data in this study was analysed using Structural Equation Model-PLS. The results of this study state that attitude, subjective norms and perceived behavioural control have a positive significant effect on the intention to invest in cryptocurrency